PENGARUH DINAMIKA PASANG SURUT TERHADAP DAERAH IRIGASI RAWA PANTAI KABUPATEN KAPUAS PROVINSI KALIMANTAN TENGAH - Zevri, Asril (Direktorat Bina Teknik Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2023)
The food crisis caused by the Covid-19 pandemic has caused the level of hunger to increase to a chronic level that is almost experienced by the whole world, including Indonesia. The increase in population with extreme climate change is a serious problem to overcome the food crisis in the next few years. The impact of climate change with changes in land use results in limited water availability in the development of irrigated land. One solution to overcome the availability of water for the development of irrigated land is to rehabilitate and improve the network of swamp irrigation areas that utilize the dynamics of tidal water levels. Pantai Swamp Irrigation Area is one of the potential lands to be developed into agricultural cultivation land. The study aims to determine the effect of tidal water level elevation on irrigated land based on hydro-topography. The study was conducted in the Pantai Swamp Irrigation Area with the water source coming from the tidal Kapuas Murung River. The method was conducted quantitatively using HEC-RAS software based on tidal data, cross-section and length of the channel, and surface elevation of irrigated land. The results showed that the influence of the tidal dynamics of the Kapuas Murung River is very dominant in irrigating the land with an average tidal water level elevation of + 1.57 m with hydro-topographic dominance included in categories B and C with an area of B 604.5 Ha and C 1201. 5 Ha.Keywords: Tides, Swamps, Hydro-topography, Sungai, Kapuas